Mettre l’intime en bande dessinée. Un dialogue avec Léna Merhej et Noémie Honein - Michela De Giacometti; Laura Odasso (L’Année du Maghreb)
In this interview, we talk with Lebanese artists Léna Merhej and Noémie Honein about their respective practices and trajectories as cartoonists, a craft for which they are particularly known. Issued from two different generations, Léna Merhej and Noémie Honein use of their singular experiences to draw and narrate the intimate, thus testifying of converging interests. In her De l’importance du poil de nez, Noémie Honein explores her experience of the disease, after discovering, at the age of twenty, that she had cancer. Translating this period of her life into comics represents to this artist a journey into the intimate relationships she maintains with her family, with a body submitted by therapies to radical transformations, and with sexuality. Born of a German mother and a Lebanese father, Léna Merhej devotes one of her first works, Laban and Jam, or how my mother became Lebanese to narrate domestic intimacy during the Lebanese war (1975-1990), the reconstruction of the country, and the 2006 summer’s war. Here, she explores her and her mother’s plural identities and family daily’s practices, and skillfully plays with the stereotypes of an imaged Lebanese identity. In 2007, Léna Merhej founded, with three Lebanese artists and cartoonists, the magazine Samandal (“salamander” in Arabic), whose vocation is to be, like this amphibian, a hybrid entity. Originally born as a publishing platform to support works from this first group of artists, the magazine soon transformed into a collective and broadened its horizons to include comics made by artists from the Arab world and beyond. To avoid censorship, Samandal published in France, in 2016, the issue entitled Ça restera entre nous (It will remain between us), an unvarnished work about sexuality which includes the illustrated boards of 27 international artists in four different languages (Arabic, French, English and Italian). By lifting the veil on the body and its multiple experiences, such as sexuality and illness, Léna Merhej and Noémie Honein invites us to explore social and political contexts in which these experiences are embedded: these women’s lives are indeed intimately intertwined with political conjunctures and the collective experience. These two artists – who now live between France and Lebanon – tell their own stories through the portrait they paint of their country of origin, Lebanon, and of their families.